2014
DOI: 10.1002/da.22232
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Therapy and Serotonin Reuptake Inhibitor Pharmacotherapy in the Treatment of Obsessive-Compulsive Disorder: A Systematic Review and Meta-Analysis of Head-to-Head Randomized Controlled Trials

Abstract: This review provides evidence that, among outpatients with OCD, behavioral therapy is more effective than SRIs, overall, but not selective SRIs. Furthermore, the combination of behavioral therapy plus an SRI is more effective than an SRI alone. These data may be used to inform the development of evidence-based treatment guidelines; however, more studies are also needed to further evaluate the relative efficacy of these interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 39 publications
(113 reference statements)
2
59
1
3
Order By: Relevance
“…Serotonin reuptake inhibitors (SRIs), CBT, and their combination are first-line treatments for OCD (Pizarro et al, 2014;Romanelli et al, 2014). The first aim of the present study was to determine whether adding TEAS to the standard treatment could enhance the therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin reuptake inhibitors (SRIs), CBT, and their combination are first-line treatments for OCD (Pizarro et al, 2014;Romanelli et al, 2014). The first aim of the present study was to determine whether adding TEAS to the standard treatment could enhance the therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by recurrent, intrusive and senseless thoughts (obsessions) and/or excessive repetitive behaviors (compulsions) aimed at reducing the associated anxiety (APA, 2000). Despite the fact that serotonin reuptake inhibitors (SRIs), such as clomipramine, and cognitive behavioral therapy (CBT) are recommended as first-line treatments for OCD (Pizarro et al, 2014;Romanelli et al, 2014), there still remains a large portion of the patients who do not make a full response (Schruers et al, 2005). A search for alternative strategies is thus important.…”
Section: Introductionmentioning
confidence: 99%
“…Adult OCD trials show that the combination of CBT and an SSRI generally does not confer additional benefits to CBT alone. The pooled results from a recent meta-analysis of pediatric and adult OCD trials concluded that the combined treatment does not provide an incremental benefit to CBT alone [48].…”
Section: Combined Treatmentmentioning
confidence: 99%
“…Nevertheless, the combined treatment seems to be significantly more effective than an SSRI alone [20,49] with a pooled effect size of g=−0.59 [5]. The pooled results from a recent meta-analysis of pediatric and adult OCD trials also showed the superiority of the combined treatment over SRI alone [48].…”
Section: Combined Treatmentmentioning
confidence: 99%
“…The hypothesis posits that the long-term experience of being excluded from the majority group leads to an increased baseline activity and/ or sensitization of the mesolimbic dopamine system, putting the individual at increased risk for the disorder 1,2 . The hypothesis may explain to a certain degree why a history of migration, membership of a disadvantaged ethnic minority group (e.g., African-American ethnicity), urban upbringing, low IQ, childhood trauma, drug abuse, hearing impairment, homosexuality 3,4 , and perhaps also autism are schizophrenia risk factors.…”
mentioning
confidence: 99%